Overview of Service Services Factors (Competence, Decency, and Communication) Towards Intranatal Care (INC) Service Satisfaction in Polindes Dahlia Sugiharjo Village Tuban - ummu qonitun (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2019)
Midwives have not implemented competency, courtesy services, communication to the satisfaction of Intranatal Care (INC) services. The purpose of this study is to identify the features of service factors (competence, courtesy, and communication) on the satisfaction of Intranatal Care (INC)The study used a descriptive research design, with a population of all women delivering INC in May - June 2018 at Polindes Dahlia, Sugiharjo Village, Tuban City. Samples were taken from all 25 pregnant women. Sample sampling technique is consecutive sampling and data collection using questionnaire, so that obtained data related to service and maternity satisfaction to service of INC.The result showed that from 25 respondents, it was found that almost all of them was competent in giving service that was 23 respondents (92%), most of them in the polite category which was 22 respondents (88%). Most of the communication is in the sufficient category of service, which is 14 respondents (56%). Almost all INC services in the good category are 18 respondents (72%).The conclusion of this study is that midwives have implemented government programs in the services of Intranatal Methods (INC), almost all midwives are competent in performing their services, most of the services are in the polite category of patients, most of their communications are in sufficient category to service, almost entirely in sufficient category in service delivery INC. Therefore, it is expected that healthcare workers improve the quality of service in serving patients